'Tis the Season for More Earth‐Friendly Plastic Toys: Sustainability is a rising concern for consumers and toymakers alike. Issue 10 (5th December 2018) - Lamontagne, Nancy D.
Abstract : Most toys purchased during the holiday season will contain some type of plastic. Although plastics are extremely versatile and durable, consumers are starting to push for toys that are also good for the environment and won't end up in the landfill when kids are done with them. Abstract : Most toys purchased during the holiday season will contain some type of plastic. Although plastics are extremely versatile and durable, consumers are starting to push for toys that are also good for the environment and won't end up in the landfill when kids are done with them